Laparoscopic Repair of a Ureterosciatic Hernia with Urosepsis - Moon, Kyong Tae; Cho, Hee Ju; Choi, Jae Duck; Kang, Jung Yoon; Yoo, Tag Keun; Cho, Jeong Man (Urology Journal, 2019)
Hernias of pelvic floor are very rare condition, and herniations of ureter into sciatic foramen are extremely rare condition which is globally reported only by 32 cases. Clinical aspects of ureterosciatic hernias appeared variously according to the degree of hydronephrosis, inflammation and infection of kidney due to ureter obstruction. Herein, we report our experience of laparoscopic repair in a patient with ureterosciatic hernia combined urosepsis.